STRATEGI PEMASARAN JASA PENDIDIKAN DALAM MENINGKATKAN CITRA SEKOLAH - Mahmud MY; Mentari Erlianto; Fransisko Chaniago; Najmul Hayat (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2022)
The purpose of this study was to find out how the marketing strategy of education in Al-Arief Islamic Private High School. This type of research is descriptive qualitative research. The method used in data collection is observation, interviews and documentation. Meanwhile, in analyzing the data, the researcher used several steps, namely by reducing, presenting and verifying the data. The results of the study have shown that overall the Al-Arief Islamic Private High School has implemented a marketing strategy for educational services that is quite good in improving the school's image. This can be seen from the existing education service marketing mix. This school has offered a product that is in accordance with the needs of the community, the fees charged by the Al-Arief Islamic Private High School are still very affordable when compared to established private schools in general, and this school is in a strategic place to carry out educational activities. The marketing strategy carried out by the Al-Arief Islamic Private High School is by carrying out promotions through student guardians, print media, social media and school output.